András Bodor and the history of classical studies in Transylvania in the 20th century - Szabó, Csaba, 1987- (Archaeopress archaeological lives., 2020)
This volume focuses on the life and academic heritage of András Bodor (1915-1999), a classicist from Transylvania. Based on a large number of unpublished documents and the major works of Bodor, the book reconstructs the life of a classicist from the periphery of Europe, a region that changed many times during the 20th century.